Activité physique, santé et vieillissement chez des femmes francophones de l'Ontario - Beausoleil, Nathalie; Martin, Geneviève (La Revue canadienne du vieillissement, 2002)
Cet article fait état d'une recherche qualitative réalisée en milieu francophone minoritaire ontarien. Les perceptions et les pratiques de l'activité physique d'une trentaine de femmes sont analysées en regard de fondements sociologiques et de discours actuels sur le vieillissement. Ces discours portent sur la responsabilité individuelle de la santé, sur les liens entre la santé, la beauté et le vieillissement, sur la pratique des sports, la masculinité et la féminité et enfin sur l'obligation de l'activité physique à tous les cycles de vie. Les résultats de l'étude auprès de femmes regroupées en trois tranches d'Çge permettent de réaliser que si ces femmes ont adopté le discours de la responsabilité individuelle pour la santé et la prévention des effets néfastes du vieillissement par l'exercice physique régulier, elles peuvent aussi etre vues comme des sujets trouvant dans leur vie quotidienne des stratégies pour ne pas subir les pressions des normes de santé et de beauté liées au vieillissement, pour faire face aux contraintes et pour développer une façon saine de vivre le vieillissement.

La santé des aînés francophones en situation linguistique minoritaire : états des lieux en Ontario - Bourbonnais, Valérie (Université d’Ottawa, 2007)
L'objectif de cette thèse est de tracer les profils comparatifs des états de santé des populations francophones et anglophones âgées de 65 ans et plus de l'Ontario en utilisant les données de l'Enquête sur la santé et les collectivités canadiennes (ESCC) recensées par Statistique Canada. Dans un deuxième temps, ces profils seront également analysés en fonction du genre. Or, trois grands volets seront examinés dans ce projet: (1) les caractéristiques socio-démographiques, (2) les états de santé déclarés et perçus, (3) ainsi que l'utilisation et la satisfaction à l'égard des services de soins de santé. L'objectif principal de cette thèse est de démontrer que le fait de vivre dans un contexte linguistique minoritaire engendre des facteurs risquant d'influencer négativement le vieillissement de la minorité sociolinguistique francophone de l'Ontario. En puisant à la discipline sociologique, une théorisation de la minorité sera utilisée afin d'appuyer la thèse avancée. Globalement les analyses révèlent un profil socioéconomique et un profil de santé plus précaires chez les aînés de la minorité francophone comparativement aux aînés de la majorité anglophone. Il est intéressant de noter que cette précarité de la santé s'exprime autant chez les hommes que chez les femmes de la minorité francophone, malgré que celle-ci s'articule différemment pour certaines variables. Quant à la prestation des services de soins de santé, les aînés de la minorité francophone sont unanimement insatisfaits de l'accessibilité, ainsi que de la qualité des services dans l'ensemble de la province ontarienne.

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Differences between the francophone and Anglophone ethno-linguistic groups in the Ontario home care setting [master's thesis, Lakehead University] - Thériault, Eric. R. (2009)